Diagnosis and Treatment of Myalgic Encephalomyelitis/Chronic Fatigue Syndrome. - Smith MEB; Nelson HD; Haney E; Pappas M; Daeges M; Wasson N; McDonagh M (Evidence report/technology assessment, 2014)
OBJECTIVES: This systematic review summarizes research on methods of diagnosing myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) and benefits and harms of multiple medical and nonmedical treatments. It identifies evidence gaps and limitations to inform future research. DATA SOURCES: Searches of electronic databases included MEDLINE® (1988 to September 2014), PsycINFO® (1988 to September 2014), and the Cochrane Library (through the third quarter of 2014). The searches were supplemented by reviewing reference lists, seeking suggestions from reviewers, and requesting scientific information from drug and device manufacturers. REVIEW METHODS: Two investigators reviewed abstracts and full-text articles for inclusion based on predefined criteria. Discrepancies were resolved through discussion and consensus, with a third investigator making the final decision. RESULTS: A total of 6,175 potentially relevant articles were identified, 1,069 were selected for full-text review, and 71 studies in 81 publications were included (36 observational studies on diagnosis and 35 trials of treatments). Eight case definitions have been used to define ME/CFS; those for ME, requiring the presence of postexertional malaise, represent a more symptomatic subset of the broader ME/CFS population. Researchers are unable to determine differences in accuracy between case definitions because there is no universally accepted reference standard for diagnosing ME/CFS. The Oxford criteria are the least restrictive and include patients who would not otherwise meet criteria for ME/CFS. Self-reported symptom scales may differentiate ME/CFS patients from healthy controls but have not been adequately evaluated to determine validity and generalizability in large populations with diagnostic uncertainty. Fourteen studies reported the consequences of diagnosis, including perceived stigma and the burden of misdiagnosis, as well as feelings of legitimacy upon receiving the diagnosis of ME/CFS. Of the 35 trials of treatment, rintatolimod compared with placebo improved measures of exercise performance; counseling therapies and graded exercise treatment (GET) compared with no treatment, relaxation, or support improved fatigue, function, and quality of life, and counseling therapies also improved employment outcomes. Other treatments either provided no benefit or results were insufficient to draw conclusions. GET was associated with higher numbers of reported adverse events compared with counseling therapies or controls. Harms were generally inadequately reported across trials. LIMITATIONS: Diagnostic methods were studied only in highly selected patient populations. Treatment trials were limited in number and had small sample sizes and methodological shortcomings. CONCLUSIONS: None of the current diagnostic methods have been adequately tested to identify patients with ME/CFS when diagnostic uncertainty exists. Rintatolimod improves exercise performance in some patients (low strength of evidence), while counseling therapies and GET have broader benefit but have not been adequately tested in more disabled populations (low to moderate strength of evidence). Other treatments and harms have been inadequately studied (insufficient evidence). More definitive studies are needed to fill the many research gaps in diagnosing and treating ME/CFS.